1964
DOI: 10.2118/579-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bacteria on Sandstone Permeability

Abstract: Detailed descriptions are given of materials, apparatus and the experimental procedure used to study the effect of bacteria on sandstone permeability. The factors affecting permeability during injection of bacterial suspensions which have been investigated are:concentration of bacteria;core permeability and median pore size;species of bacteria, mode of aggregation and relative size;injection rate or pressure differential;mean pressure; anddepth of penetration of bacteria. The investigation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…In some cases pressure was measured at a serious of points along the core. There is general agreement that the injection of large volumes of dense bacterial suspensions produces a progressive reduction in permeability (Hart, Fekete and Flock, 1960;Kalish et al, 1964;Raleigh and Flock, 1965;Jenneman et al, (983). The most severe plugging occurs at, or close to, the injection face.…”
Section: Microbial Activities and Meor Plugging And Penetration Of Rementioning
confidence: 99%
See 3 more Smart Citations
“…In some cases pressure was measured at a serious of points along the core. There is general agreement that the injection of large volumes of dense bacterial suspensions produces a progressive reduction in permeability (Hart, Fekete and Flock, 1960;Kalish et al, 1964;Raleigh and Flock, 1965;Jenneman et al, (983). The most severe plugging occurs at, or close to, the injection face.…”
Section: Microbial Activities and Meor Plugging And Penetration Of Rementioning
confidence: 99%
“…The greater the concentration of cells injected, the greater the degree of plugging. There is a concentration effect: a given number of cells causes more plugging if injected at low concentration than at high concentration (Hart et al~1960; Kalish et at., 1964). Kalish et at.…”
Section: Microbial Activities and Meor Plugging And Penetration Of Rementioning
confidence: 99%
See 2 more Smart Citations
“…Although previous investigations have revealed that bacteria can penetrate deeply into porous media (Jenneman et al, 1985;Kalish et al, 1964), a complete understanding of the penetration behavior of bacteria is lacking. Furthermore, there is limited amount of publications on microbial penetration/plugging study on chalk as earlier studies were conducted on sandstones (Jenneman et al, 1985;Kalish et al, 1964), micromodels (Afrapoli et al, 2011), glassbeads (Armstrong and Wildenschild, 2012) and sandpacks (Sarkar et al, 1994;Weiss et al, 1995). In all these porous media the pore sizes are considerably larger than in chalk rocks.…”
Section: Introductionmentioning
confidence: 99%